Magnetic polarity influence on machining performance of magnetic field-assisted edm - Mohd Efendee, Awang (2020)
Electrical discharge machining (EDM) is one of the non-traditional machining techniques where it is commonly used in the mould and die making industry. However, the lengthy machining time in EDM process leads to low material removal rate (MRR). While increasing MRR by increasing peak current value, it affects the quality of surface finish. The EDM process offers a wide-range of machining parameters and hybrid EDM techniques can be manipulated in solving the EDM drawbacks. The present research aims to study the magnetic polarity influence on magnetic field-assisted EDM. In addition to MRR, electrode wear rate and surface roughness (Ra) of the sample illustrate the effectiveness of the EDM process. The installation of magnetic tools in the EDM machining area was implemented to study its improvements in EDM process. Moreover, the description of magnetic polarity impact in magnetic field-assisted EDM (MFAEDM) remains unacquainted. In the experiment, the EDM Charmiles Roboform22 utilized kerosene and cylindrical Ø25 mm graphite electrode to spark 2 mm depth of cut on AISI 420.mod tool steel. Peak current in the range of 8 A to 24 A and 50 µs to 100 µs of pulse time were designated along with 0.54 Tesla for both North-South (N-S) and North–North (N-N) polarity. The results show that MFAEDM technique enhanced MRR by 13% as compared to conventional EDM at 24 A and 100 µs. Surface roughness produced by MFAEDM was reduced by 16% and 20% respectively for peak current of 8 A and 24 A. N-S polarity combination improved Ra value as much as 10% for peak current of 8 A and 8% for 24 A as compared to N-N combination. The reason is the magnetic field squeezes and purifies spark-eroded process by trapping evaporated debris promptly onto the magnetic bar. MFAEDM causes removal of machining debris more efficiently and is able to attain high-efficiency of MRR. Thus, it improves surface finish quality to meet the demands of modern industrial application.